2023
DOI: 10.1177/03009858231176563
|View full text |Cite
|
Sign up to set email alerts
|

Coelomic fluid of asteroid echinoderms: Current knowledge and future perspectives on its utility for disease and mortality investigations

Abstract: Coelomic fluid surrounds the internal organs of asteroid echinoderms (asteroids, otherwise known as sea stars or starfish) and plays an essential role in the immune system, as well as in the transport of respiratory gases, nutrients, waste products, and reproductive mediators. Due to its importance in physiology and accessibility for nonlethal diagnostic sampling, coelomic fluid of asteroids provides an excellent sample matrix for health evaluations and can be particularly useful in disease and mortality inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 126 publications
1
3
0
Order By: Relevance
“…Unexpectedly, papulae additionally express diverse GPCRs, secreted proteins, TFs and lineage-specific coding sequences, suggesting this tissue has a wider sensory and regulatory role. Coelomocytes isolated from wild COTS are probably derived from the perivisceral coelom, which has a diversity of functions in COTS and other echinoderms, including immunity and wound healing, nutrient transport and waste removal [36,4951]. We found that the coelomocyte transcriptomes are enriched in genes associated with microfilament function, consistent with phagocytes being a dominant cell type in this tissue as observed in other echinoderms [36,51].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Unexpectedly, papulae additionally express diverse GPCRs, secreted proteins, TFs and lineage-specific coding sequences, suggesting this tissue has a wider sensory and regulatory role. Coelomocytes isolated from wild COTS are probably derived from the perivisceral coelom, which has a diversity of functions in COTS and other echinoderms, including immunity and wound healing, nutrient transport and waste removal [36,4951]. We found that the coelomocyte transcriptomes are enriched in genes associated with microfilament function, consistent with phagocytes being a dominant cell type in this tissue as observed in other echinoderms [36,51].…”
Section: Discussionsupporting
confidence: 77%
“…Amongst these TFs are six nuclear receptors that are known in vertebrates to be influenced by seasonal hormones [43,52]. Putative nuclear receptor ligands, such as steroids, have been detected in COTS and in other echinoderms, and may be playing a seasonal role in reproduction [51,5355]. These findings are consistent with the existence of conserved deuterostome – or maybe even bilaterian or metazoan – mechanisms to regulate circannual physiological changes via the activation of nuclear receptors and partner TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Papulae additionally express diverse GPCRs, secreted proteins, TFs, and lineage-specific genes, suggesting this tissue has a wider sensory and regulatory role than previously appreciated. Coelomocytes isolated from wild COTS are probably derived from the perivisceral coelom, which has a diversity of functions in COTS and other echinoderms, including immunity and wound healing, nutrient transport, and waste removal [ 36 , 49 51 ]. We found that the coelomocyte transcriptomes are enriched in genes associated with microfilament function, consistent with phagocytes being a dominant cell type in this tissue as observed in other echinoderms [ 36 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these co-expressed TFs in the summer are 6 nuclear receptors that are known in vertebrates to be influenced by seasonal hormones [ 43 , 52 ]. Putative nuclear receptor ligands, such as steroids, have been detected in COTS and in other echinoderms, and may be playing a seasonal role in reproduction [ 51 , 53 55 ]. These findings suggest there are conserved deuterostome—and maybe even bilaterian or metazoan—mechanisms to regulate circannual physiological changes via the activation of nuclear receptors.…”
Section: Discussionmentioning
confidence: 99%